Catastrophic failure of the Accolade I hip arthroplasty stem: a retrieval analysis study. Issue 4 (July 2020) - Wylde, Christopher W; Jenkins, Elizabeth; Pabbruwe, Moreica; Bucher, Thomas
Purpose: Modular Morse tapered femoral arthroplasty stems have been used for many years with great success and minimal complications. 1 stem, the Accolade by Stryker is noted to have increased failure when used in combination with LFIT V40 CoCr or the MITCH CoCr femoral heads. The failure has been in the form of corrosion, metallosis, fretting and trunnion fracture. This paper explores 10 cases with trunnion failure. Methods: A retrospective retrieval analysis of ten femoral stems retrieved at four different centres across Western Australia over a 3-year time frame. Inclusion criteria for this analysis included the use of Accolade 1 TMZF femoral stem plus either a MITCH or LFIT modular head. Results: 10 Accolade I (Stryker) stems were retrieved as part of the analysis, 6 with the LFIT V40 36-mm femoral head and 4 with a MITCH TRH femoral head. Average in situ time was 8.9 years. The hips were revised for either trunnion dislocation (6 cases) or trunnion fracture (4 cases). A characteristic destructive wear pattern of the femoral taper (trunnion) a "bird beak" appearance was present in all stems. This wear pattern created excessive movement and loosening resulting in a trunnion/head dislocation or brittle fracture of the trunnion. Conclusions: Catastrophic femoral neck fracture was likely due to a combination of material composition mismatch and mechanically assisted fretting corrosion at the head-neck junction leading to gross metallosis and failure. We suggest a recall on patients with an Accolade 1 stems in combination with a 36-mm or above LFIT or MITCH head, and for these patients to have clinical and radiological review.